Inhaled Gases as Therapies for Post–Cardiac Arrest Syndrome: A Narrative Review of Recent Developments - Hayashida, Kei; Miyara, Santiago J.; Shinozaki, Koichiro; Takegawa, Ryosuke; Yin, Tai; Rolston, Daniel M.; Choudhary, Rishabh C.; Guevara, Sara; Molmenti, Ernesto P.; Becker, Lance B. (Frontiers in Medicine, 2021)
Despite recent advances in the management of post-cardiac arrest syndrome (PCAS), the survival rate, without neurologic sequelae after resuscitation, remains very low. Whole-body ischemia, followed by reperfusion after cardiac arrest (CA) contributes to PCAS, for which established pharmaceutical interventions are still lacking. It has been shown that a number of different processes can ultimately lead to neuronal injury and cell death in the pathology of PCAS, including vasoconstriction, protein modification, impaired mitochondrial respiration, cell death signaling, inflammation, and excessive oxidative stress. Recently, the pathophysiological effects of inhaled gases including nitric oxide (NO), molecular hydrogen (H2), and xenon (Xe) have attracted much attention. Herein, we summarize recent literature on the application of NO, H2, and Xe for treating PCAS. Recent basic and clinical research has shown that these gases have cytoprotective effects against PCAS. Nevertheless, there are likely differences in the mechanisms by which these gases modulate reperfusion injury after CA. Further preclinical and clinical studies examining the combinations of standard post-CA care and inhaled gas treatment to prevent ischemia-reperfusion injury are warranted to improve outcomes in patients who are being failed by our current therapies.